Report on identifying a protocol to elicit flowering in Brachiaria humidicola with photoperiod management - Florián, David; Hernández, Luis Miguel; Castiblanco, Valheria (International Center for Tropical Agriculture, 2019)
Two Genotypes of Brachiaria humidicola (A and B) were planted on the grounds of CIAT headquarters in Palmira during 2018 – 2019, 10 lamps were placed in the lot to evaluate 6 different photoperiods (1 - 6) with Light in 2 different wavelength range (W.R.) α and β, for this, 17 samples were carried out on the variables height, vigor, chlorophyll content and number of inflorescences; a total of 93 field work were carried out to support the trial, finding that the photoperiod 5 in the W.R. β and 3 photoperiod in the W.R. α for the B genotype show significant differences (p <0.05, Tukey) with respect to the other treatments for height and number of inflorescences, performing the statistical analysis in the SAS software. As to the seed production, it was found that any light stimulus generates greater seed production, despite the conditions under which the crops were made and the method of harvest used. I order to refine the protocol and validate the results in bigger genotype sample another trial with the 2 most efficient treatments was proposed for 2020, focusing on number of inflorescences and seed production.